Increased diversity of beneficial rhizobia enhances faba bean growth - Marcela Mendoza-Suárez; Turgut Yigit Akyol; Marcin Nadzieja; Stig U. Andersen (Nature Communications)
Abstract Legume-rhizobium symbiosis provides a sustainable nitrogen source for agriculture. Nitrogen fixation efficiency depends on both legume and rhizobium genotypes, but the implications of their interactions for plant performance in environments with many competing rhizobium strains remain unclear. Here, we let 399 Rhizobium leguminosarum complex sv. viciae strains compete for nodulation of 212 faba bean genotypes. We find that the strains can be categorised by their nodule occupancy profiles into groups that show distinct competitive interactions and plant growth-promoting effects. Further, we show that the diversity of strains occupying root nodules affects plant growth and is under plant genetic control. These insights provide a basis for re-designing rhizobium inoculation and plant breeding strategies to enhance symbiotic nitrogen fixation in agriculture.